Testing the neutrality of money, labor, and capital in Pakistan's agriculture sector - Mulk, Waleed; Ahmad, Shakil; Younas, Waqar; Ali, Syed Yawar (Asian Journal of Economics and Empirical Research, 2024)
This study investigates the neutrality of money in Pakistan's agriculture sector by analyzing semi-annual data from 1991S1 to 2019S2. We employ the impulse response function, variance decomposition, Johansen cointegration, VECM, and the Granger causality test. The Johansen cointegration approach demonstrates a continuous relationship between the variables over time. The Granger causality test indicates no short-term causal relationship between agricultural productivity and the broad money supply. On the other hand, agricultural production has a short-term causal relationship with inflation and capital. Long-term outcomes corroborate the empirical findings of the cointegration test, suggesting the existence of a cointegration connection. The impulse-response and variance decomposition tests indicate that the broad money supply has a statistically significant positive effect on short- and long-term agricultural productivity. On the other hand, inflation has both short-term and long-term detrimental effects on agricultural productivity. Meanwhile, short-term and long-term labor and capital shocks symmetrically affect agricultural productivity. Consequently, our results refute the long-term money neutrality hypothesis. The results of this paper will assist policymakers and researchers in gaining a more comprehensive understanding of the impact of inflation, labor, capital, and the broad money supply on Pakistan's emerging economy.